Promoting Sketching in Introductory Geoscience Courses: CogSketch Geoscience Worksheets. (23rd September 2017) - Garnier, Bridget; Chang, Maria; Ormand, Carol; Matlen, Bryan; Tikoff, Basil; Shipley, Thomas F.
Abstract: Research from cognitive science and geoscience education has shown that sketching can improve spatial thinking skills and facilitate solving spatially complex problems. Yet sketching is rarely implemented in introductory geosciences courses, due to time needed to grade sketches and lack of materials that incorporate cognitive science research. Here, we report a design‐centered, collaborative effort, between geoscientists, cognitive scientists, and artificial intelligence (AI) researchers, to characterize spatial learning challenges in geoscience and to design sketch activities that use a sketch‐understanding program, CogSketch. We developed 26 CogSketch worksheets that use cognitive science–based principles to scaffold problem solving of spatially complex geoscience problems and report observations of an implementation in an introductory geoscience course where students used CogSketch or human‐graded paper worksheets. Overall, this research highlights the principles of interdisciplinary design between cognitive scientists, geoscientists, and AI researchers that can inform the collaborative design process for others aiming to develop effective educational materials. Abstract : In their paper "Promoting sketching in introductory geoscience courses: CogSketch geoscience worksheets, ‐ Garnier and colleagues provide details on how an interdisciplinary team used CogSketch to produce Sketch Worksheets in undergraduate geoscience education. In a field trial over a semester they were able to increase the frequency in which sketching assignments were set (as they no longer needed to be hand marked). Moreover, they were able to design exercises which permitted student interactions with their sketches in ways that are beneficial and not possible with pen and paper.